Photoelectrode Fabrication of Dye-Sensitized Nanosolar Cells Using Multiple Spray Coating Technique - Chien-Chih Chen; Chen-Ching Ting (International Journal of Photoenergy)
This paper presents a spray coating technique for fabricating nanoporous film of photoelectrode in dye-sensitized nanosolar cells (DSSCs). Spray coating can quickly fabricate nanoporous film of the photoelectrode with lower cost, which can further help the DSSCs to be commercialized in the future. This paper analyzed photoelectric conversion efficiency of the DSSCs using spray coated photoelectrode in comparison with the photoelectrode made with the doctor blade method. Spray coating can easily control transmittance of the photoelectrode through the multiple spray coating process. This work mainly used a dispersant with help of ultrasonic oscillation to prepare the required nano-TiO2 solution and then sprayed it on the ITO glasses. In this work, a motor-operated conveyor belt was built to transport the ITO glasses automatically for multiple spray coating and drying alternately. Experiments used transmittance of the photoelectrode as a fabrication parameter to analyze photoelectric conversion efficiency of the DSSCs. The influencing factors of the photoelectrode transmittance during fabrication are the spray flow rate, the spray distance, and the moving speed of the conveyor belt. The results show that DSSC with the photoelectrode transmittance of ca. 68.0 ± 1.5% and coated by the spray coating technique has the best photoelectric conversion efficiency in this work.